Eff ect of cellulosic matter and container size on cultivation and yield of oyster mushroom Pleurotus ostreatus - Burhan Majed Nassar, Ahmed Mahali Abed, Ahmed Mohammed Turki, Mustafa Nadhim Owaid, (Journal of Medicinal Herbs and Ethnomedicine, 2015)
When cultivation the oyster mushrooms, we must put ability use locally low-cost wastes in this agriculture viz. houses and shops wastes. The ability of paper wastes (cardboard) and wheat straw were estimated in the oyster mushroom Pleurotus ostreatus production in plastic bottles of different volumes from wastes of houses in Hit city compare as using polyethylene bags. The results showed that the best significant (P < 0.05) crop reached to 143.8 g on bags that capacity 1.5 kg of wheat straw, followed by a rate 64.8 g on the same substrate in 0.55 kg plastic bottles. The larger number of flushes was 2.2 flushes/bag for the wheat straw in a bottle (0.55 kg), followed 2.0 flushes/bag by the cardboard in a bag of capacity 1.5 kg. Higher significant (P < 0.05) weight of the body was 120.4 g when grown in a bag 1.5 kg of wheat straw. The cardboard was showed the biological efficiency 32.5% compared with the wheat straw (control) 25.7% while the higher biological efficiency was 60.7% followed 45.9% for the wheat straw on bags that capacity 0.5 kg and bottle 0.1 kg, respectively.